Development of an Efficient Analytical Method for the Extraction and Analysis of Biocide Contents from the Textile Test Specimens on LC-DAD - Muhammad Jahangir; Uzman Khan (Journal of Analytical Methods in Chemistry)
Biocides are frequently used in the manufacturing of textiles that are in direct contact with human skin. Recently regulated biocides do not have validated methods for testing; so, their presence cannot be estimated in the consumer products. Hence a rapid method was developed for the separation and quantitative analysis of biocide contents (2-methyl-4-isothaizolin (MIT), 5-chloro-2-methyl-4-isothaizolin-3-one (CIT), 2-octo-4-isothaizolin-3-one (OIT), and 5-chloro-2-(2,4-dichlorophenxy) phenol (triclosan)) from the textile test specimens. Test specimens were extracted with methanolic sonication and purified by centrifugation and filtration. Biocide contents were separated at C18 column with 0.4% acetic acid: methanol (1 : 1 v/v) under isocratic mode and detected at 280 nm wavelength. Pretreatment factors such as extraction solvent, extraction method, dilution ratio, and extraction time were optimized initially and plotted calibration curve showed regression (r2 ≥ 0.9995) in the range of 1.0–5.0 mg L−1. Recoveries were between 95% and 108% with the relative standard deviation ≤ 4%. Limits of detection (LODs) were between 0.06 mg L−1 and 0.12 mg L−1 and limits of quantification (LOQs) were between 0.21 mg L−1 and 0.38 mg L−1. From the results, conclusion was made that the method can achieve the purpose of quantitative detection and the analysis of real test specimens verified the reliability of this method.